Arctic ionosphere modelling : five related papers - Air Force Cambridge Research Laboratories (U.S.)
Research supported by the Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, L.G. Hanscom Field, Bedford, Massachusetts. Ionospheric Physics Laboratory Project 5631. Contributing authors: J. Buchau, R.A. Wagner, G.J. Gassmann, C.P. Pike, M.G. Hurwitz. AD0748796 (from http://www.dtic.mil). "16 May 1972." Includes bibliographical references (page 56). Coordinate conversion and other computer programs for arctic ionospheric research by J. Buchau and M.G. Hurwitz. Modelling the arctic F-layer, by C.P. Pike. Model of arctic sporadic E, by G.J. Gassmann. Modelling the auroral E-layer, by R.A. Wagner. Instantaneous versus averaged ionosphere, by J. Buchau. Mode of access: Internet.